Conflict Management in Interpersonal Communication - Harutyunyan, Gohar; Baldryan, Susanna (Armenian Folia Anglistika, 2013)
The article examines differences in the expression of interpersonal conflicts and management tactics in such different cultures as American and Armenian. Through a survey, an attempt is also made to consider the role and significance of this phenomenon in the Armenian culture.